An Electron Dynamics Mechanism of Charge Separation in the Initial‐Stage Dynamics of Photoinduced Water Splitting in XMnWater (X=OH, OCaH) and Electron–Proton Acceptors. Issue 12 (23rd June 2015) - Yamamoto, Kentaro; Takatsuka, Kazuo
Abstract An electron dynamics mechanism of charge separation in the initial stage of excited‐state reactions of the class of XMnOH2⋅⋅⋅A<alternatives> <![CDATA[${ \to }$]]> <inline-graphic xlink:href="ark:/27927/pgj2ffrf7wq" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>XMnOH⋅⋅⋅HA (X=OH or OCaH; A=N‐methylformamidine, guanidine, imidazole, or ammonia cluster) is reported. The dynamic effect of calcium doping is also revealed. This study provides a novel factor to be considered in designing efficient systems for photoinduced water splitting.